Topographic paracentral corneal thickness with pentacam and orbscan: effect of acoustic factor - González-Pérez, Javier (2011)
Purpose: To evaluate the effect of an acoustic factor (AF) on the comparison of central corneal thickness (CCT) and peripheral corneal thickness (PCT) measurements with Orbscan II and Pentacam. Methods: The CCT and PCT at 1, 2, and 3 radial distances from the corneal apex were measured using Orbscan II and Pentacam in 22 right eyes of 22 healthy adults (7 men, 15 women). Three measures were obtained from each 1 of the 25 points measured and then compared to gauge the agreement between both devices at the corneal center and anular areas located at 1-, 2-, and 3-mm distances from the central measurement. Orbscan II readings were considered with and without an AF correction. Results: Pentacam provides statistically significant higher values than Orbscan II does at all the 25 locations analyzed (P,0.001). With a few exceptions, the average difference was fairly constant between 20 and 40 mm for all the corneal locations. A high correlation existed between central readings (r2=0.927; P,0.001) and average thickness at each one of the annular areas being analyzed (r2=0.897 at 1 mm, r2=0.876 at 2 mm, and r2=0.870 at 3 mm); Pentacam minus Orbscan II value averaged for all the points changed from 228610 to 22269 mm after the removal of the AF in Orbscan II. Conclusions: Central and peripheral measurements of the corneal thickness obtained with Orbscan II and Pentacam are significantly different. The removal of the AF in Orbscan II renders lower mean differences but decreases the agreement between both systems and potentially induces an overestimation of CCT and PCT by Orbsan II compared with Pentacam.